The effects of Ad disliking on purchase intention. - Ong, Rachel Cuiting. (2008)
This experimental study aims to investigate the influence of ad disliking on consumers’ purchase intentions. Ad disliking was hypothesized to lead to lower purchase intentions than when ads are liked. In addition, it was also hypothesized to have greater effects on purchase intentions when consumers have low need for cognition, when they are under low-involvement conditions and when they are not brand-loyal.